Measuring Educational Justice In The Dynamic Flow Of National Legal Politics - Marpaung, Rindu Erwin; Purba, Jan Sardo Pratama; Manalu, Dormauli; Saragih, Maria Stefani; Manihuruk, Fitrikiara Noffansa; Tampubolon, Cici Gamiarsi (STABN RADEN WIJAYA WONOGIRI, 2024)
Legal politics plays a pivotal role in shaping the direction and substance of education policy in Indonesia. This study aims to examine how legal politics influences the development of the national education system and its implications for the principle of educational justice. Employing a qualitative method through literature reviews, the research analysis of legal documents, academic works, policy reports, and statistical data. The findings indicate that, although education policies normatively guarantee the right to education, their implementation continues to reflect disparities in access and quality across regions and social groups. The lack of participatory lawmaking and the absence of evidence-based policy evaluation hinder the realization of substantive justice. Therefore, reform in legal politics is urgently needed—one that is inclusive, socially just, and focused on empowering marginalized communities. This study advocates for long-term legal strategies that transform education into a genuine instrument of social equity and national development.